WESTERN ESOTERICISM AS AN OBJECT OF RELIGIOUS STUDIES RESEARCH - Pavel Nosachev (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2013)
This article presents a short excursus into the history of research on western esotericism. At the beginning the basic terms esoterica and esotericism are defi ned. Then the history of societies and academic chairs devoted to research on the subject is examined. The source for research on the subject is the Eranos Circle. Later authors such as Frances Yates took up the study which was continued and developed in the volumes authored by Antoine Faivre and Wouter Hanegraaff. Resorting to generalities in describing the various branches of thought on the subject, the author defi nes three main schools: the American School, the Old European School, and finally the New European School. The principle characteristics of the American School is the acknowledgement of the reality of esoteric experience and a tendency to override the border dividing the researcher and the phenomenon researched as well as attempting to popularize the subject in wide sectors of society. The Old European School is characterized by its extremely critical attitude to esotericism, seeing in it little more than a deviation on the path of the development of culture and religion. The New European School, on the other hand, is guided by a post-modern approach to research on this subject, which leads to the constant study of the problem of dialogue and demands a pluralistic attitude in regard to various forms of esotericism. Another characteristic of this school is the intention to include the study of esotericism as an accepted academic discipline. Some basic problems which face the contemporary researcher of this topic are studied by the author separately. The idea of combining the study of esotericism with the study of theology is also touched upon, pointing out the basic contradiction and incompatibility separating the two subjects. Two approaches for Christian researchers are defined — the approach of the tree and the modernistic approach